Explotando vulnerabilidades en el protocolo MODBUS TCP/IP (2016)
This document is an experimental and bibliographic recompilation about SCADA systems, where the Modbus protocol is often used controlling public services systems and critical infrastructures. SCADA systems are specially designed to run on computers in production control, providing communication with field devices (autonomous controllers, PLCs, etc.) and controlling the process automatically from a computer. (Pérez, 2014) This software is designed for internal use by companies and researchers within the organization being not generic enough to be used in any type of architecture, protocol or system (Queiroz, Mahmood, & Tari, 2011), Inside the protocol communications there are automatic instruments that measures and control all actions on the action field, but the HMI is a necessary thing to have when taking full control of a process is mandatory, or to execute an action. These systems are highly critical which makes different malicious users find attractive to exploit the vulnerabilities of these systems, this in order to prove themselves or economic purposes. These vulnerabilities are basic in nature, allowing anyone with an average level of knowledge exploit it, making the risk and the attack probability much greater. Grupo de Investigación: Modelamiento y Simulación Computacional. -- Área: seguridad informática. -- Tema: sistemas SCADA.